Plan de negocios para la creación de un patio de comidas para fomentar el emprendimiento en los beneficiarios del bono de desarrollo humano, cantón Quevedo, año 2014 - Mero Franco, Jefferson Cristóbal (2015)
This research project aims to diagnose the problems that are the beneficiaries of the Human Development Bond Quevedo Canton, in the province of Los Rios, the aim is to present a business plan for the creation of a food court and encourage entrepreneurship in beneficiaries BDH, Quevedo Canton, 2015; because these people need arise at a particular time and leave the group of extreme poverty. Making merit the National Development Plan and Good Living, and despite the efforts made by each individual that is not possible, therefore it is considered that if capabilities, creativity, skills and attitudes, along with teamwork unite it achieve a entrepreneurial culture, this with the support of universities and institutions that contribute to the knowledge and skills required. So in the research they were used as methods: statistical, qualitative, inductive, deductive, descriptive field, literature review, surveys, interviews; non-experimental and cross-sectional design. And it has also proposed a business plan to encourage such projects, using advertising media campaign alternative media like facebook, word of mouth and .....